Deformation mechanisms of CoCrFeMnNi high-entropy alloy under low-cycle-fatigue loading. (15th August 2021) - Lu, Kaiju; Chauhan, Ankur; Tirunilai, Aditya Srinivasan; Freudenberger, Jens; Kauffmann, Alexander; Heilmaier, Martin; Aktaa, Jarir
Abstract: Plastic deformation during low-cycle fatigue (LCF) in equiatomic face-centered cubic (FCC) CoCrFeMnNi high-entropy alloys (HEAs) is accumulated by dislocation substructure formation, which leads to crack initiation. Whilst these substructures have been reported before, little has been done to clarify their formation mechanisms and the effects of strain amplitude, cycle number and grain orientation. In this study, cyclic deformation behavior and microstructural evolution of CoCrFeMnNi were examined for two different grain sizes at room temperature. Microstructural investigations by transmission electron microscopy showed that, while the dislocation structures at low strain amplitude (0.3%) mainly consisted of planar slip bands, at higher strain amplitudes (0.5% and 0.7%), wavy-substructures including veins, walls, labyrinth and cells prevailed. Slip mode also changes from initially planar-slip to wavy-slip with cycle numbers. Dislocations in veins, walls, labyrinth and cells are found to have different Burgers vectors, suggesting that apart from wavy-slip, multiple-slip also contributes to their formation. Moreover, distinct dislocation substructure in grains is dictated more by the constraints from neighboring grains rather than by their orientation. Additionally, the formation of various dislocation structures in a single grain is also linked to the constraint effects from the neighboring grains. Graphic abstract: Image, graphical abstract